2015
DOI: 10.1007/s11095-015-1651-0
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed Macrophage Mannose Receptor Targeted Nanocapsules- Mediated Cargo Delivery Approach for Eradication of Resident Parasite: In Vitro and In Vivo Studies

Abstract: Results demonstrated that mannose ligand grafted chitosan nanocapsules could improve selective delivery of AB into macrophages via interactions with overexpressed mannose receptors thus reduce undesirable toxicity. Study provides evidence for MnosCNc-AB potential to leishmaniasis therapeutics and presents valuable therapeutic strategies for combating chronic macrophage-resident microbial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…Zia et al (2015) showed that killing of intracellular C. albicans after treatment with amphotericin B polyglutamic acid nanoparticles was higher than with Ambisome® (Zia et al, 2015). Amphotericin B is also used for the treatment of infections caused by Leishmania spp., which is an intracellular parasite, so that intense investigation has been done in order to enhance drug antiparasitic effects throughout nanostruturation (Asthana et al, 2015; Jain et al, 2015; Bose et al, 2016). …”
Section: Nanopreparations For Polyenesmentioning
confidence: 99%
“…Zia et al (2015) showed that killing of intracellular C. albicans after treatment with amphotericin B polyglutamic acid nanoparticles was higher than with Ambisome® (Zia et al, 2015). Amphotericin B is also used for the treatment of infections caused by Leishmania spp., which is an intracellular parasite, so that intense investigation has been done in order to enhance drug antiparasitic effects throughout nanostruturation (Asthana et al, 2015; Jain et al, 2015; Bose et al, 2016). …”
Section: Nanopreparations For Polyenesmentioning
confidence: 99%
“…The same team improved the targeting capability of chitosan, using mannosylated chitosan (Mnos-CS) copolymer, subsequently formulated in a nanocapsule system (MnosCNc) for the delivery of AmpB. 121 Using nanocapsules, DL of 9%-10% (w/w) was obtained. In vivo results showed that more drug was delivered by mannosylated nanocapsules than by CNC or plain AmpB in both liver and spleen.…”
mentioning
confidence: 99%
“…Chemotherapy for VL is based on the use of antimony. However, the emergence of resistance has transformed medical management to the use of amphotericin B (AmB) for VL treatment [2,3]. Notably, targeted intracellular delivery of AmB has now emerged as a first-line medical strategy to facilitate pathogen clearance.…”
mentioning
confidence: 99%
“…Notably, targeted intracellular delivery of AmB has now emerged as a first-line medical strategy to facilitate pathogen clearance. The development of improved drug delivery formulations that include nanotechnology-based targeted therapeutics that target infected cells and tissues could improve treatment outcomes [3,4]. …”
mentioning
confidence: 99%
See 1 more Smart Citation